The Child and the Latina Immigrant: Reimagining the Southern California Imaginary in Héctor Tobar's The Barbarian Nurseries. - Ropp, Sarah (Western American Literature)
A literary criticism of the 2011 book "The Barbarian Nurseries" by Héctor Tobar is presented. It discusses the novel's story about 11-year-old Brandon Torres-Thompson and his younger brother who are left alone with Mexican housekeeper Araceli when their parents left them following domestic trouble. It discusses the representation of the children's subjectivity and their capacity to creatively interpret their environments.